Reading Their Book of Faith: North American Muslims and Their Interpretations of the Qur’an in the Post 9/11 Era - Grafton, David D. (Dialog, 2009)
This article seeks to provide an overarching view of the North American Muslim conversation about interpreting the Qur’an in a post 9/11 world. While most Western critiques of Islam focus on reading the texts of Islam, the author argues that one must also listen to the contemporary intra-Muslim conversation about their own text, in order to faithfully understand the Muslim perspective. In this conversation, the author provides evidence for a plurality of social-political views among Muslims and notes that the post 9/11 North American context is alive and well with such faith conversations.